The Nuremberg Trials - Downie, E. A. (London William Heinemann Ltd, 1962)
This American Experience production draws upon rare archival material and eyewitness accounts to re-create the dramatic tribunal that defines trial procedure for state criminals to this day.
Include Index
Keywords: Germany -- Nuremberg Trial of Major German War Criminals (Germany : 1945-1946)